Order topologies, and continuity of homomorphisms - Tanaka, Yoshio (Topology Proceedings, 2025)
We consider ordered additive groups (rings, fields), and continuity of homomorphisms between them, in terms of their (algebraic) order topologies. Also, we give related examples.